PERAN SERVANT LEADERSHIP KEPALA DESA DALAM MEMODERASI PENGARUH PERILAKU KEWIRAUSAHAAN DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA BUMDES DI KOTA PARIAMAN - Zahid Nugrah Arafah; Elfiswandi Elfiswandi; Yulasmi Yulasmi (Komunitas Manajemen Kompetitif, 2026)
This study investigates the influence of entrepreneurial behavior and organizational commitment on the performance of Village-Owned Enterprises (BUMDes) in Pariaman City. Furthermore, it examines the moderating role of servant leadership in these relationships. The research employs Structural Equation Modeling (SEM) with SMARTPLS as the analytical tool. The sample comprises the entire population of 25 BUMDes, with three managers from each enterprise (chairperson, secretary, and treasurer) as respondents, yielding a total of 75 participants, in accordance with Mayor’s Regulation No. 30 of 2018. The findings reveal that entrepreneurial behavior, organizational commitment, and servant leadership each have a significant effect on BUMDes performance. Additionally, servant leadership moderates the relationship between entrepreneurial behavior and performance, as well as between organizational commitment and performance. The moderation analysis further indicates that servant leadership functions as a quasi-moderator. These results highlight the critical role of servant leadership in enhancing organizational outcomes within community-based enterprises